Improvement of the Energy Utilization Efficiency of the V-Ti-Magnetite Reduction Process with Rotary Hearth Furnace - Wei, Ruirui; Lun, Zhigang; Lv, Xuewei; Hu, Tu; Bai, Chenguang (Journal of Mining and Metallurgy, Section B: Metallurgy, 2015)
In order to improve the energy utilization of rotary hearth furnace (RHF), some methods were raised to solve the problem. Through changing the inlet angle of the nozzle, a higher and more uniform temperature field can be got. Thus, the burden in the furnace can be heated to the reduction temperature in a relatively shorter time. By using multilayer pellets technology, the energy can be utilized as much as possible. However the top layer pellets would be reoxidized when the middle and bottom layer pellets were reduced. The average metallization of the reduced pellets get the maximum value at 25 min which is consistent with the reality operation.